2021
DOI: 10.2147/opth.s280508
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Characteristics of Extraocular Muscles in Myasthenia Gravis Patients with Ocular Manifestations: A Case–Control Study

Abstract: Purpose To analyze radiological characteristics of the extraocular muscles (EOMs) in myasthenia gravis (MG) patients with ocular manifestations. Patients and Methods This retrospective case–control study included all MG cases with ocular manifestations, who attended a neuro-ophthalmology clinic at a university hospital, Bangkok, from April 2009 to June 2018. They experienced double vision and ophthalmoplegia. Control participants had normal eye movements. Orbital scans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Similar to the EOM histopathological findings, imaging of the EOMs in patients with MG with chronic refractory ocular symptoms, found evidence of muscle atrophy and fatty replacement ( 52 ). Interestingly, fatty replacement with larger muscle volume was evident in the EOMs of a pilot case series (feasibility study) earlier in their disease course ( 68 ), whereas those with a longer disease duration showed muscle atrophy ( 69 ).…”
Section: Resultsmentioning
confidence: 98%
“…Similar to the EOM histopathological findings, imaging of the EOMs in patients with MG with chronic refractory ocular symptoms, found evidence of muscle atrophy and fatty replacement ( 52 ). Interestingly, fatty replacement with larger muscle volume was evident in the EOMs of a pilot case series (feasibility study) earlier in their disease course ( 68 ), whereas those with a longer disease duration showed muscle atrophy ( 69 ).…”
Section: Resultsmentioning
confidence: 98%
“…[ 1 2 3 ] However, three recent studies have revealed that fat replacement and atrophy are not so uncommon in these muscles. [ 4 5 6 ] MG related to anti-MuSK antibodies is known to cause atrophy of the tongue and facial muscles. However, extraocular involvement was not extensively reported.…”
Section: Discussionmentioning
confidence: 99%
“…Lueangaram et al . [ 4 ] showed a statistically significant difference in the muscle volumes of an MG group compared to a control group. Moreover, the atrophy of extraocular muscles in MG was more in chronic cases, although it occurred early in some.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…44,77,97 In CPEO, an increase in signal intensity on a T1w scan has been described within EOM, 81 as well as a quantitative increase in T2 relaxation time, 80 89 In addition, central hypo-intensities were observed on T2w scans with fat suppression in myasthenia gravis. 90 In myasthenia gravis, fat replacement appears to be less frequently reported in literature than in CPEO. In CFEOM Type II, T1w imaging shows bright signal regions and longitudinal fissures in the LR and the MR, also indicative of fat replacement.…”
Section: Mri and Fat Replacementmentioning
confidence: 99%